“It Made Me a More Self-Directed Learner”: The Non-Formal, Informal and Transformative Learning of People Living with HIV/AIDS - Lisa M. Baumgartner (Adult Education Research Conference, 2014)
The nature of learning for those living with HIV/AIDS was explored. Learning occurred in non-formal settings. Informal learning occurred including self-directed, incidental and tacit learning. Prior learning affected current learning. The transformative learning that happened confirmed previous studies’ findings. Findings have implications for HIV/AIDS educators.